Cinacalcet Targets the Neurokinin-1 Receptor and Inhibits PKCδ/ERK/P65 Signaling to Alleviate Dextran Sulfate Sodium-Induced Colitis - Chen, Yuehong; Liu, Huan; Zhang, Qiuping; Luo, Yubin; Wu, Liang; Zhong, Yutong; Tang, Zhigang; Pu, Yaoyu; Lu, Chenyang; Yin, Geng; Xie, Qibing (Frontiers in Pharmacology, 2021)
Objective: Inflammatory bowel disease is an immune-mediated chronic inflammatory disease of the gastrointestinal tract for which curative drugs are currently not available. This study was performed to assess the therapeutic effects of cinacalcet on dextran sulfate sodium (DSS)-induced colitis. Methods: Primary macrophages obtained from bone marrow and the macrophage cell line RAW264.7 were used to examine the inhibitory effect of cinacalcet on cytokine production, the PKCδ/ERK/P65 signaling pathway, and NF-κB P65 translocation. Colitis was induced using DSS to assess the treatment effect of cinacalcet. Bioinformatics approaches were adopted to predict potential targets of cinacalcet, and a drug affinity responsive target stability (DARTs) assay was performed to confirm binding between cinacalcet and potential target. Results:In vivo analysis showed that cinacalcet reduced the disease activity score, prevented shortening of the colon, diminished inflammatory cell infiltration, and protected the structural integrity of the intestinal wall. Cinacalcet also reduced production of the inflammatory cytokines TNFα, IL-1β, and IL-6 in the colon and sera of mice with DSS-induced colitis. In vitro studies revealed that cinacalcet suppressed the translocation of P65 and inhibited production of the inflammatory cytokines IL-1β and IL-6. Mechanistic studies revealed that the target of cinacalcet was neurokinin-1 receptor (NK1R) and their binding was confirmed by a DARTs assay. Furthermore, the inhibition of NK-κB P65 activation was found to occur via the suppression of PKCδ/ERK/P65 signaling mediated by cinacalcet. Conclusion: Cinacalcet inhibits the activation of NF-κB and reduces the production of inflammatory cytokines by suppressing the PKCδ/ERK/P65 signaling pathway via targeting NK1R, suggesting that it can be used to treat inflammatory diseases, particularly colitis.